ผลของพอลิบิวทิลีนซักซิเนตและโวลลาสโทไนต์ต่อสมบัติเชิงกลและสมบัติเชิงความร้อนของเพ็ตใช้แล้ว - กลศาสตร์ นีรนาทมานิต (จุฬาลงกรณ์มหาวิทยาลัย, 2015)
This study aimed to improve the mechanical properties, thermal stability and biodegradability of post consumed-poly(ethylene terephthalate) (p-PET) by incorporation of poly(butylene succinate) (PBS), a very flexible biodegradable aliphatic polyester and wollastonite (WT), a needle-shaped inorganic filler. First, p-PET was melt blended with five loadings of PBS (10-50 wt%) on a twin screw extruder. The extrudates were pelletized and then fabricated into test specimens by an injection molding. The tensile strength (TS), impact strength (IS), elongation at break (EB), degree of crystallinity (Xc), water absorption and biodegradability were found to be improved, but at the expense of reduction of the Young’s modulus (E), flexural strength (FS) and thermal stability of the blends caused by the addition of PBS into p-PET. Among the p-PET/PBS blends, the 60/40 (wt%/wt%) p-PET/PBS blend exhibited the optimal IS and TS. This blend ratio was further filled with four loadings of wollastonite (10, 20, 30 and 40 parts per hundred resin, phr). The composites of p-PET/PBS filled with various loadings of wollastonite were also prepared by the process as above. The TS, E and thermal stability of the composites were then found to be improved, while EB, IS, FS, Xc, flammability and water absorption were decreased. However, the composite containing 40 WT had the optimum properties.